Issues of application of anti-monopoly legislation provisions to the activities of digital platforms - I. N. Dekhtyar; E. N. Konina (Гуманитарные и юридические исследования)
The article is devoted to the study of topical problems of improving antimonopoly legislation in order to regulate public relations arising in the activities of digital platforms. The article analyzes the provisions of the latest regulatory legal acts of the Russian Federation and foreign states, dedicated to the determination of the legal status of digital platforms. Analysis of foreign legislation made it possible to identify existing approaches to the legal regulation of digital platforms, which can act as a guideline in the development of regulatory legal acts of the Russian Federation, as well as contribute to the prevention, identification and suppression of commercial practices of digital platforms that harm legal relations in the field of protection of competition and prevention of illegal monopolistic activity. The normative and doctrinal definitions of the concepts of «digital platform», «big data», «network effects» are considered. The author’s assessment of the correspondence of these concepts to the real economic activity of digital platforms is given. It is concluded that it is advisable to consolidate the definitions of the concepts of «digital platform», «big data», «network effects», «ecosystem» in the antimonopoly legislation of the Russian Federation. The need to amend the antimonopoly legislation of the Russian Federation is substantiated in order to take into account the influence of «big data» and «network effects» on the state of real or potential competition in the markets in which digital platforms operate. The problems of analyzing the commodity market in the digital economy and the activities of digital platforms have been identified. The conclusion is made about the discrepancy between the established methods of analyzing the commodity market to determine the dominant position and the state of competition in the event that the subjects of economic activity are digital platforms. New effective approaches to analyzing the state of the market when considering cases of violation of antimonopoly legislation committed by digital platforms are proposed.